Análise fisico-química e legalidade em bebidas de laranja - Figueira, Ricardo [UNESP]; Nogueira, Andressa Milene Parente [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP]; Ducatti, Carlos [UNESP]; Queiroz, Elvio Cardoso [UNESP]; Pereira, Aline Graziele da Silva [UNESP] (My University, 2010)
The aim of this paper was to measure the total soluble solids content (°Brix), titrable total acidity (AT) and ratio in orange beverages, such as frozen concentrated juice, not from concentrate juice, nectar and soft drink and to compare them with their Quality and Identity Standards (PIQ) published by the Ministry of Agriculture, Livestock and Food Supply (MAPA) and Codex Alimentarius. Four orange frozen concentrated juices, twenty two juices, seven nectars and thirteen orange soft drinks were analyzed. All frozen concentrated orange juices were in agreement with Codex Alimentarius. The majority of not from concentrated orange juices and soft drinks was in accord to Brazilian legislation. The orange nectars could not be compared with the standards because they are not published by MAPA or Codex Alimentarius.

O objetivo do presente trabalho foi mensurar o teor de sólidos solúveis totais (°Brix), acidez titulá- vel (AT) e ratio em sucos, sucos concentrados, néctares e refrigerantes de laranja comerciais e compará-los com os Padrões de Identidade e Qualidade (PIQ) estabelecidos pelo Ministério da Agricultura, Pecuária e Abastecimento (MAPA) e Codex Alimentarius. Vinte e duas amostras de sucos, quatro de sucos concentrados, sete de néctares e treze de refrigerantes de laranja foram analisadas. Todas as amostras de sucos concentrados apresentaram resultados condizentes com Codex Alimentarius. A grande maioria das amostras de sucos e refrigerantes comerciais estava dentro dos padrões da legislação brasileira. Os néctares de laranja não puderam ser comparados com padrões legais, pois estes são inexistentes tanto no MAPA quanto no Codex Alimentarius.
Keywords: Juice; Nectar; Soft drink; Adulteration; Quality; Citrus sinensis; Análise físico-química; Bebidas não alcoólicas; Laranja